Tier 2 oral language and early reading interventions for preschool to grade 2 children: a restricted systematic review. Issue 1 (2nd January 2022) - Goldfeld, Sharon; Beatson, Ruth; Watts, Amy; Snow, Pamela; Gold, Lisa; Le, Ha ND; Edwards, Stuart; Connell, Judy; Stark, Hannah; Shingles, Beth; Barnett, Tony; Quach, Jon; et al.
ABSTRACT: This systematic review investigated small-group Tier 2 interventions to improve oral language or reading outcomes for children during preschool and early primary school years. Literature published from 2008 was searched and 152 papers selected for full-text review; 55 studies were included. Three strength of evidence assessment tools identified a shortlist of six interventions with relatively strong evidence: (a) Early Reading Intervention; (b) Lonigan and Philips (2016) Unnamed needs-aligned intervention; (c) PHAB+WIST (PHAST)/PHAB+RAVE-O; (d) Read Well-Aligned intervention; (e) Ryder and colleagues' (2008) Unnamed Phonological Awareness and Phonics intervention; and (f) Story Friends. Investigation of intervention componentry found common characteristics included 3–5 students, 4–5 sessions per week, minimum 11-week duration, content covering a combination of skills, modelling and explicit instruction, and trained personnel. Shortlisted interventions provide a useful foundation to guide further interventions and inform educators and policymakers seeking to implement effective evidence-based interventions in the early years of schooling.